Epidemiological Study of Dengue Hemorrhagic Fever (DHF) With Increased Incidence of Serum Glutamic Pyruvic Transaminase (SGPT) Levels at Aura Syifa Hospital Kediri: Studi Epidemiologi Demam Berdarah Dengue (DBD) dengan Kejadian peningkatan kadar Serum Glutamic Pyruvic Transaminase (SGPT) di Rumah Sakit Aura Syifa Kediri - Kurniasari, Mia Ashari; Nurziah, Anggit Saputri Okta (Universitas Muhammadiyah Sidoarjo, 2021)
Dengue fever virus is an infectious disease that can infect others if bitten by Aedes aegypti mosquito. The virus has the potential to attack cells in the hepar organs so that the hepar is inflamed, swollen, and liver function is disrupted, and there is severe bleeding. The increase in transaminase enzymes as well as hepatomegaly is a frequent sign in dbd sufferers, thus reinforcing the notion that the course of dengue hemorrhagic fever (DHF) disease can affect hepar or liver organs. The presence of such events will increase the level of Serum Glutamic Pyruvic Transaminase (SGPT) and Serum Glutamic Oxaloacetic Transaminase (SGOT) in dengue fever patients. The purpose of this study is to find out the epidemiological study of Dengue dengue fever with the increase in SGPT and SGOT levels in dengue fever patients at Aura Syifa Kediri Hospital. This research method uses descriptive research design and total sampling technique for 1 month. Samples obtained for 1 month amounted to 15 samples. The results showed that from a sample of 15 respondents as many as 3 samples (20%) for high SGPT levels above normal and normal results as many as 12 samples (80%). The conclusion of this study shows that the value of SGPT levels has increased by 20% and is still above normal, but still have to be alert to small values.